SpatiotemporaI distribution of oxytocin receptor in uterine tissues associated with corpus luteum location in cows - Tsuchiya, S; Cerbito, W A; Wijayagunawardane, M P B; Miyamoto, A; Takagi, M; Miyazawa, K; Sato, K (The Indian Journal of Animal Sciences, 2012)
The bovine uterine horns were characterized for local concentration and distribution of oxytocin receptor (OT·R) with reference to the location of the regressing corpus loteum, lntercaruncle endometrial and myometrial tissues were collected at spatially 3 different parts of the uterine horn (proximal, medial, distal) and I part in the body of the uterus. At follicular and postovulation stages, the distriblution of OT·R levels in endometrial tissues in relation to the regressing CL were not significantly different among locations but the OT·R levels in the uterine body were lower than in the uterine horns. Mean endometrial OT·R of ipsilateral horn to the regressing CL showed significantly higher (P